Development of gene expression panels to determine prostate cancer - Gerashchenko, G.V.; Rynditch, A.V.; Kashuba, V.I. (Доповіді НАН України, 2019)
The aim of this investigation is to prove a modified algorithm for statistical approaches to develop gene expression
panels for the detection of prostate tumors. According to Classification and Regression tree models and RE differences
between adenocarcinoma (T) and adenoma (A) groups, we have chosen 31 transcripts for MDR analysis.
Among them, there were 15 transcripts of (epithelial-mesenchymal transition (EMT) and prostate-cancer associated
(PrCa-associated) genes and 16 transcripts of cancer-associated fibroblasts (CAF), tumor-associated macrophages
(TAM), immune-associated genes (IAG)), which have shown some datasets with high statistical parameters. The
highest diagnostic levels are manifested by expression panels developed from all 5 gene groups: PCA3, HOTAIR,
ESR1, IL1R1 (Se = 0.97, Sp = 0.85, Ac = 0.93, OR = 204); CDH2, KRT18, PCA3, HOTAIR, ESR1, IL1R1 (Se = 1.0,
Sp = 0.8, Ac = 0.93, OR > 500). We propose an improved algorithm for the gene expression data analysis to develop
diagnostic panels with good and excellent diagnostic levels for the prostate tumor stratification in a group of patients
from the Ukrainian population. Our data require a more detailed analysis and a larger cohort of patients with
prostate tumor. Досліджено адаптацію модифікованого алгоритму статистичного підходу для розробки експресійних панелей для детекції раку передміхурової залози. За даними моделей класифікації та регресії й статистично
значущими відмінностями відносної експресії між групами аденокарцином та аденом, серед досліджуваних генів відібрано 31 транскрипт для MDR аналізу. Серед них 15 транскриптів з груп генів епітеліальномезенхімального переходу та генів, асоційованих з раком передміхурової залози, і 16 транскриптів з груп
генів пухлиноасоційованих фібробластів, пухлиноасоційованих макрофагів та імуноасоційованих генів.
З цих груп отримано ряд панелей з високими статистичними показниками. Найвищі показники діагностичних рівнів мали експресійні панелі, які розроблені з усіх п’яти груп генів: PCA3, HOTAIR, ESR1, IL1R1
(Se = 0,97, Sp = 0,85, Ac = 0,93, OR = 204); CDH2, KRT18, PCA3, HOTAIR, ESR1, IL1R1 (Se = 1,0, Sp = 0,8,
Ac = 0,93, OR > 500). Запропоновано модифікований алгоритм для аналізу даних експресії генів, який може бути використаний для розробки діагностичних панелей з добрим та високим діагностичними рівнями
для стратифікації раку передміхурової залози на групі пацієнтів з української популяції. Одержані дані
потребують подальшого аналізу на більшій вибірці пацієнтів з раком передміхурової залози. Исследована адаптация модифицированного алгоритма статистического подхода для разработки экспрессионных панелей для детекции рака простаты. Согласно данным моделей классификации и регрессии, а
также статистически значимым отличиям относительной экспрессии между группами аденокарцином и
аденом, среди исследуемых генов отобрано 31 транскрипт для MDR анализа. Среди них 15 транскриптов
из групп генов эпителиально-мезенхимального перехода и генов, ассоциированных с раком простаты, и 16
транскриптов из групп генов опухолеассоциированных фибробластов, опухолеассоциированных макрофагов и иммуноассоциированных генов. Из этих групп было получено ряд панелей с высокими статистическими показателями. Самые высокие показатели диагностических уровней имели экспрессионные панели, полученные со всех пяти групп генов: PCA3, HOTAIR, ESR1, IL1R1 (Se = 0,97, Sp = 0,85, Ac = 0,93,
OR = 204); CDH2, KRT18, PCA3, HOTAIR, ESR1, IL1R1 (Se = 1,0, Sp = 0,8, Ac = 0,93, OR > 500). Предложен
модифицированный алгоритм для анализа данных экспрессии генов, который может быть использован
для разработки диагностических панелей с хорошим и высоким диагностическими уровнями для стратификации рака простаты на группе пациентов из украинской популяции. Полученные данные требуют более детального анализа на большей выборке пациентов с раком простаты.